Time to question the NHS diabetes prevention programme. - Barry, E; Roberts, S; Finer, S; Vijayaraghavan, S; Greenhalgh, T (BMJ Publishing Group Ltd, 2015)
Public Health England’s focus on individual behaviour change is unlikely to stem the epidemic of type 2 diabetes.